Alternative Ways to Obtain Human Mesenchymal Stem Cells from Embryonic Stem Cells - Nikita Onyanov; Olga Glazova; Nawar Sakr; Tatyana Krokunova; Julia Krupinova; Pavel Volchkov (Cells)
Differentiation approaches to obtain mesenchymal stem cells (MSCs) have gradually developed over the last few decades. The problem is that different protocols give different MSC types, making further research difficult. Here, we tried three different approaches to differentiate embryonic stem cells (ESCs) from early mesoderm to MSCs using serum-containing or xeno-free differentiation medium and observed differences in the cells’ morphology, doubling rate, ability to form colonies, surface marker analysis, and multilineage differentiation potential of the obtained cell lines. We concluded that the xeno-free medium best fits the criteria of MSCs’ morphology, growth kinetics, and surface marker characterization. In contrast, the serum-containing medium gives better potential for further MSC differentiation into osteogenic, chondrogenic, and adipogenic lineages.